Standardization of marketed Ayurvedic formulation, Balaguloochyadi kashayam-physicochemical, microbial evaluation and ephedrine content - Tabassum Asif Khan, Rashmi Mallya, Anjali Gohel (Journal of Applied Pharmaceutical Science, 2016)
The present study reports the physicochemical, microbial and analytical (marker based) standardization of an Ayurvedic marketed formulation- Balaguloochyadi kashayam (Rajah Ayurveda). Physicochemical standardization was performed by determining organoleptic properties, pH, specific gravity and total solid content. Total bacterial count and total fungal count studies were performed for microbial standardization. Marker based standardization involved development and validation of a High Performance Thin Layer Chromatography (HPTLC) method for quantitative determination of a chemical marker viz. ephedrine present in Bala, major herb of Balaguloochyadi kashayam as per the standard protocols. The physicochemical and microbial tests were performed in triplicate and average results were calculated. A new, accurate, precise and robust HPTLC method for estimation of ephedrine in Balaguloochyadi kashayam was developed on Camag Linomat-5 using silica gel 60 GF254 as stationary phase and toluene: chloroform: n-propanol: ethanol: formic acid (6: 3: 1: 2: 1, v/v/v/v/v) as mobile phase. The validation studies were performed as per International Conference on Harmonization- Quality (ICH-Q2 (R1)) guidelines. The results of these experiments can be used by manufacturers as a reference for controlling the quality of Balaguloochyadi kashayam formulations prior to release for marketing.
Keywords: Herbal formulation, standardisation, Balaguloochyadi kashayam, ephedrine, HPTLC.